1997
DOI: 10.1002/jlac.199719971115
|View full text |Cite
|
Sign up to set email alerts
|

Dihydrocolchicine 8,12‐Endoperoxide: A Novel Starting Material for Convenient Syntheses of the Allocolchicinoids N‐Acetylcolchinol O‐Methyl Ether and Androbiphenyline

Abstract: Optically pure dihydrocolchicine‐8,12‐endoperoxide 2 is used as the starting material for the synthesis of some bioactive allocolchicinoids. Depending on the reaction conditions and reagents employed, different modifications of the C ring of colchicine (1) are achieved. Triphenylphosphane deoxygenation of 2 leads to the well known N‐acetylcolchinol O‐methyl ether (NCME, 6, 40% yield from 1). Treatment of the endoperoxide 2 with CH3OH/CH2Cl2/silica gel provides the plant alkaloid androbiphenyline (11) in a yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 28 publications
4
19
0
Order By: Relevance
“…When our sample of NCME (21) was recorded in CDCl3, a 69:24:7 ratio of three species, 21a:21b:21c was observed. The 1 H and 13 C NMR spectroscopic data for two of these species matched with those reported by Brecht et al (71:29, 21a:21b) 22 and all three of those reported by Takubo [α −88.6 (c 0.67, MeOH)}.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…When our sample of NCME (21) was recorded in CDCl3, a 69:24:7 ratio of three species, 21a:21b:21c was observed. The 1 H and 13 C NMR spectroscopic data for two of these species matched with those reported by Brecht et al (71:29, 21a:21b) 22 and all three of those reported by Takubo [α −88.6 (c 0.67, MeOH)}.…”
Section: Resultssupporting
confidence: 86%
“…21 As expected, the 1 H and 13 C NMR spectroscopic data recorded for the sample of NCME (21) prepared in this study using DMSO-d6 as the solvent matched well with these other, previously reported data. A smaller number of synthetic samples of NCME have 1 H and 13 C NMR spectroscopic data using CDCl3 as the solvent: Brecht et al 22 reported a 71:29 ratio of species for NCME in CDCl3, whilst Takubo et al 23 reported a 65:25:10 ratio of species. When our sample of NCME (21) was recorded in CDCl3, a 69:24:7 ratio of three species, 21a:21b:21c was observed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These, and additional results from experiments with carbonyl, cyclic ketal and thioketal derivatives were attributed to electrostatic interaction between approaching singlet oxygen and the heteroatom 416,417 . Similar electronic effects were observed in studies on singlet oxygen [4 + 2]-cycloaddition to the naturally occurring alkaloid (−)-colchicine 418,419 , but the opposite facial selectivity was reported for the isomeric (−)-isocolchicine 420 .…”
Section: Cycloaddition Of Singlet Oxygen With 13-dienessupporting
confidence: 63%
“…From the chemical point of view, the methyl tropolone ring is the most intriguing portion of the molecule, on which a large number of reactions can be performed, such as facile acid and alkaline hydrolysis (4), benzylic acid rearrangement (5), ipso-and telenucleophilic substitutions (6,7), Diels-Alder cycloadditions with several hetero-and carbodienophiles (8), singlet oxygen addition (9) and photochemical rear-*To whom correspondence should be addressed at: Dipartimento di Chimica, Universitá della Basilicata, Via N. Sauro 85, 85100 Potenza, Italy. Fax: ϩ39 0971 202223; e-mail: dauria@unibas.it rangement (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%